Environmental and Health Risks of People Living in Batulayang Landfills, West Kalimantan Province, Indonesia - Indah Nurdiana; Rossie Wiedya Nusantara Nusantara; Akhmad Yani (Poltekkes Kemenkes Surabaya, 2025)
Waste management activities at landfills negatively impact the environment and health risks for humans living around landfill sites. Of the many impacts produced, the perception of the community living around the landfill location is important in knowing the community's response to the effects produced. This research aims to analyze the perception of people living around the Batulayang landfill site, which has a distance of 100 to 2 km, regarding environmental and health problems. This research is a cross-sectional study. The data in this research were obtained from interviews using a questionnaire. This research has received ethical approval No. 13/KEPK-PK.PKP/VI/NP/2024 by the Pontianak Ministry of Health Polytechnic Research Ethics Review Commission. According to the research findings, public perception about property value decline showed a p-value of 0.018 (< 0.05), while public perception about the increase in mosquito populations near the Batulayang landfill had a p-value of 0.016 (≤ 0.05). This indicates a statistically significant difference between the two based on location or residential distance. Additionally, there is a statistically significant difference in health history between respondents from the two groups (p-value > 0.05), and for skin diseases, a significant difference was observed with a p-value of 0.005 (≤ 0.05). Government intervention with communities living close to landfill sites is critical to ensure their health and welfare.